Ciclos de greves : o peso da variável salário na literatura internacional e nacional de greves - Ponce, Pedro Augusto (Universidade Federal de São Carlos, 2010)
This research continues the study of strikes and collective action in Brazil. From the conception that the strikes have a cyclical character, determination of complex and changeable, this study shows the weight that the variable pay - traditionally seen as the main determinant of strikes - has in determining the conflict at different times given. The salary issue is in Brazil and the world's central theme of labor relations, but is not, in most cases, the main determinant of the phenomenon striker. In the theories of collective action and strikes a set of variables competes in explanatory power. In Brazil, for example, from the inaugural 1978 strikes, most of the demands of national strikes have been directly or indirectly pay, it does not presume that only wages could explain the reduction or expansion in the number of strikes. Through a mapping of national and international discussion of the topic and theoretical and methodological assumptions that guide this work, we try to compare the weight given to variable pay relative to other explanatory variables such as inflation and unemployment in determining the conflict industrial. To achieve this purpose, is part of the main explanations of cycles European, American, Latin American and national strikes, the authors grouped according to year and location of the debate. But this general observation hides different approaches that establish causal relationships or no causation between the variables considered. Thus, the American model said the strikes fall when unemployment is rising which is not shown to be true for Europe. On this continent, the wages seem to figure in the background, sometimes as a result of unemployment, as shown by the Danish case. In Brazil noted that the wages figured in the foreground and led to the outbreak of strikes in 1978 does not mean that they explain, by itself, the expansion or reduction of labor.
Keywords: Greves; Ciclos de greves; Ação coletiva; Strikes; Cycle of strikes; Collective action; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO